“Just Like You Killed a Member of my Family”: Revenge in the Film the Killing of a Sacred Deer (2017) - Annisa Rahmani (Universitas Pendidikan Indonesia (UPI), 2021)
Revenge is often manifested in aggressive attacks to seek justice. Many literary works, including films, have brought up this issue by emphasizing the cruelty of revenge. In this regard, this research intends to unfold another interpretation for revenge. It is presented by the vindictive character of the Film The Killing of a Sacred Deer (2017). In this film, Martin takes revenge on Steven implicitly. The analysis draws on the theory of revenge from McCullough (2008). As the theory highlights, taking revenge exposes desires for revenge. These desires are natural responses from the vindictive person who gets offended by the transgressor. For instance, Martin desires to confirm the crime done by Steven and wishes Steven to admit it. Martin then begins to transform his desire into several acts of revenge: (1) implicit intimidation, (2) intruding Steven’s private space, (3) casting ‘spell’, and (4) committing homicide. Further, Bordwell, Thompson, and Smith's (2017) cinematic features also manifest evidence for these implicit attacks. Therefore, the analysis shows that Martin retaliates to Steven in implicit aggression. Martin reveals his vengeance in the film through his reasons and the manifestation of acts for revenge. Keywords: Film analysis, Revenge, The Killing of a Sacred Deer